The Influence Of Husband Support On The Activity Of Pregnant Women In The Class Of Pregnant Women In Kemuning Village, Tarik Sidoarjo District - Ante Indraningtyas; Nita Dwi Astikasari (Master of Public Health Program Universitas STRADA Indonesia, 2023)
Pregnant women who come to visit the class of pregnant women will be monitored again at the next hamul class visit. Lack of awareness of pregnant women of the importance of classes of pregnant women, causing the low implementation of classes of pregnant women. So that pregnant women do not know the benefits of classes of pregnant women, mothers do not understand about the health of pregnant women and influence the decision of mothers in the use of health facilities (Prasetyowati, 2012). Based on a preliminary study in the Kemuning village of Tarik Sidoarjo District from interviews conducted with 10 pregnant women shows that there is still a lack of active visits of mothers attending classes of pregnant women in the Kemuning village of Tarik Sidoarjo District. The design of this study included a cross sectional analytic study with a survey approach (survey research). The population in this study were all trimester III pregnant women visiting Kemuning Village, Tarik Sidoarjo District in 2020, sampling with accidental sampling techniques and the sample size in this study were 23 respondents. The independent variable in this study is husband support with ordinal scale and the category is good, quite less, whereas for the dependent variable is the activity of joining the class with a nominal scale and categorized as active and inactive. This research was conducted in January to July 2020 in Kemuning Village, Tarik Sidoarjo District and measured using a questionnaire for the independent variables and the MCH book for the dependent variable. In collecting data from respondents the next step taken by researchers is data processing by editing, coding, scoring, tabulating, data entry, and cleaning. Data analysis in this study used the chi square test. Chi square test results show the value of ρ value (0.005) <α (0.05) which means that H0 is rejected and H1 is accepted, meaning that there is a relationship between husband support and active class of pregnant women. Social support and family and husband are very influential on the pregnancy process of a mother, if the pregnancy is accompanied by full support from her husband and family, then the pregnancy process will go well which will indirectly affect the health of the mother and the fetus she is carrying.